Phosphorus forms and availability assessed by 31P-NMR in successively cropped soil - Gatiboni L.C.* (2005)
Soils under no-tillage gradually increase in organic matter and phosphorus (P) content from the top layer. Because of lack of knowledge about the organic phosphorus fraction contribution to plant nutrition, this research was conducted to estimate the availability of phosphorus fractions to plants. Soil samples of a very clayey Rhodic Hapludox that received 0, 156 and 312 kg P ha-1 were submitted to 15 successive crops in pots without replacing P extracted by plants. 31P nuclear magnetic resonance analysis was performed to detect P fractions before cultivation and after the sixth, ninth and fifteenth crops. Inorganic phosphorus was the unique P fraction acting as P source to plants in soils with previous P addition. Contribution of organic P was observed only when inorganic P content was extremely low, with plants showing severe P stress. Contribution of organic P was not enough to supply the required P for normal plant growth. Copyright © Taylor & Francis, Inc.